The Changing Paradigm of Radiotherapy in the Elderly Population. Issue 4 (July 2017) - Pfeffer, Myer Raphael; Blumenfeld, Philip
Abstract : Abstract: There is increasing awareness of the special needs for care of the elderly cancer patient. Newer precise conformal radiotherapy techniques allow the safe delivery of higher doses of radiotherapy to the target tumor while reducing the dose to surrounding critical organs. This has led to a shortening of radiotherapy protocols for both curative and palliative indications. We review these novel techniques and protocols and the published clinical studies that include elderly patients treated with these techniques. Despite the fact that the elderly are a growing significant proportion of cancer patients, and the need for radiotherapy in the elderly is expected to rise with increasing life expectancy, they are underrepresented in most clinical studies of radiotherapy, and there are few studies specifically investigating radiotherapy in the elderly. The treatment of early-stage primary lung cancer with stereotactic body radiotherapy is a prime example how new highly conformal techniques and shortened treatment protocols are changing the approach to radiotherapy in the elderly. With improved imaging and radiotherapy treatment precision, it is expected that such techniques will become increasingly used in other cancer sites. It is important for radiation oncologists to be aware of the special needs of the elderly cancer patient and in particular to assess these patients based on functional status and not only chronological age. In addition, geriatric oncologists should be aware of modern radiotherapy techniques that can be particularly appropriate for the elderly patient.